Pedley, Paul. Essential law for information professionals - Ivana Radenović (Vjesnik Bibliotekara Hrvatske)
Pedley, Paul. Essential law for information professionals. 4th ed. London: Facet Publishing, 2019. XLVI, 349 str.: ilustr.; 24 cm. ISBN 9781783304356